INFLUENCE OF HIGH ADRENALIN DOSES ON THE MORPHOFUNCTIONAL STATUS OF RATS EPIPHYSIS UNDER THE CONDITION OF ITS HYPOFUNCTION - Pshychenko, V.V.; Cherno, V.S.; Davydenko, R.M.; Gavrilyuk, I.M.; Kucher, O.O. (World of Medicine and Biology, 2020)
The work highlights the effect of adrenaline on morphology and functional activity of epiphysis in the conditions of its hypofunction. The study was performed on 24 sexually mature males of Wistar rats, with a body weight of 150-220 g. Animals were simulated hypofunction of epiphysis and administered a single dose of adrenaline hydrochloride (0.5 mg/kg) intraperitoneally. It is established that the effect of a high dose of adrenaline is accompanied by the development of destructive processes in the epiphysis cells and is characterized by vacuolization of the cytoplasm with further development of the intracellular structures lysis. These morphological features indicate the development of necrotic processes and, accordingly, the loss of pinealocytes.